2017
DOI: 10.1063/1.4991496
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origin of wall slip during flow of an entangled DNA solution in microfluidics: Flow induced chain stretching versus chain desorption

Abstract: Despite the relevance and importance of slip, a fundamental understanding of the underlying molecular mechanisms of wall slip in polymer flow is still missing. In this work, we investigate the slip behavior of an entangled DNA solution at a molecular scale using a confocal microscope coupled to a microfluidic device. From microscopic measurement, we obtain both the velocity profile and conformation of polymeric chains by visualizing DNA molecules during flow on various surfaces (ranging from weak to strong int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…However, this no-slip boundary condition will not be valid for many complex fluids, such as polymer solutions. Especially at higher polymer concentrations things become even more complicated when a thin polymer-depleted layer of much lower viscosity than the bulk solution forms at the solid boundary, in which the surface wettability plays a crucial role [73][74][75][76][77]. One of the open questions in centrifugal spinning that has not been dealt with in detail, to our knowledge, is the effect of nozzle material on the final fiber morphology.…”
Section: Polymer Solution-wall Interactionsmentioning
confidence: 99%
“…However, this no-slip boundary condition will not be valid for many complex fluids, such as polymer solutions. Especially at higher polymer concentrations things become even more complicated when a thin polymer-depleted layer of much lower viscosity than the bulk solution forms at the solid boundary, in which the surface wettability plays a crucial role [73][74][75][76][77]. One of the open questions in centrifugal spinning that has not been dealt with in detail, to our knowledge, is the effect of nozzle material on the final fiber morphology.…”
Section: Polymer Solution-wall Interactionsmentioning
confidence: 99%
“…In a first study, calf thymus DNA (polydisperse, average molecular size of ≈75 kbp) was prepared at three different concentrations in an aqueous salt buffer corresponding to three levels of entanglement: Z = 24, 60, and 156 entanglements per chain [210]. Here, it was found that only high levels of entanglement (Z [214]. Finally, recent methods in optical coherence tomography and velocimetry measurements have further confirmed the existence of shear banded flow profiles in highly entangled DNA solutions [215].…”
Section: Shear Banding In Entangled Dna Solutionsmentioning
confidence: 99%
“…It was found that interfacial chain disentanglement results in wall slip beyond the stress overshoot, and disentanglement generally produces tumbling motion of individual DNA in the entangled solutions under shear. More recently, the phenomenon of wall slip was studied by single molecule imaging near adsorbing and non-adsorbing boundaries[214]. Finally, recent methods in optical coherence tomography and velocimetry measurements have further confirmed the existence of shear banded flow profiles in highly entangled DNA solutions[215].…”
mentioning
confidence: 99%
“…To mitigate the influence of edge instabilities, shearbanding experiments with sample edges wrapped in plastic films [5], in large-aspect-ratio shear cells with small gaps [8,[27][28][29] and using a special cone-partitioned-plate rheometer [30] have been conducted. However, it is still debatable whether these procedures truly eliminate the edge instabilities [14].…”
Section: Introductionmentioning
confidence: 99%